2020
DOI: 10.21203/rs.3.rs-25489/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Breastfeeding and acute lymphoblastic leukaemia: potential leukemogenesis in children in developing countries

Abstract: Background:Breastfeeding (BF) in infancy is associated with a decreased risk of acute lymphoblastic leukaemia (ALL). However, most of the studies were conducted in developed countries, neglecting developing countries where mothers might be exposed to different carcinogenic substances which could be transferred through breastmilk.Methods: This is a case-control study which was conducted in the major paediatric cancer centre in Syria. Data of case and control groups were obtained from the hospital’s records. Onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…However, a study from Denmark did not find a correlation between ALL and age intervals [ 25 ]. One case-control study in Syria found no association between number of siblings and ALL [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, a study from Denmark did not find a correlation between ALL and age intervals [ 25 ]. One case-control study in Syria found no association between number of siblings and ALL [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, high educational level included having a university degree or higher. This system is used in Syria as these groups have distinguished features, and it was used previously in many studies [ 26 , 27 , 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations